LC–TOF-MS/MS and GC-MS based phytochemical profiling and evaluation of wound healing activity of Oroxylum Indicum (L.) Kurz (Beka) - Abdulhafiz, Ferid; Reduan, Mohd Farhan Hanif; Hisam, Anwar Hazim; Mohammad, Ibtihal; Abdul Wahab, Ikarastika Rahayu; Abdul Hamid, Fathin Faahimaah; Mohammed, Arifullah; Nordin, Muhammad Luqman; Shaari, Rumaizi; Bakar, Luqman Abu; Kari, Zulhisyam Abdul; Wei, Lee Seong; et al. (Frontiers in Pharmacology, 2022)
Background: Beka (Oroxylum indicum (L.) Kurz) has been used as a culinary herb and natural remedy by the local communities in Malaysia. The leaf of O. indicum is traditionally used for the treatment of diarrhea, high blood pressure, and improving digestive health. Objectives: The present study was conducted to evaluate the phytochemical constituents and wound healing properties (in vitro and in vivo models) of aqueous and ethanol extracts of O. indicum leaves. Methods: The total phenolic (TPC) and total flavonoid (TFC) contents in the plant extracts were determined by the spectrophotometric methods. Further, the extract was characterized by Liquid Chromatography Time‐of‐Flight Mass Spectrometry (LC-TOF-MS/MS) and Gas Chromatography-Mass Spectrometry (GC-MS). The wound healing activity was assessed using the in vitro scratch wound-healing assay and in vivo excisional wound model. Results: The results show the ethanol leaves extract had the higher TPC (164 mg GAE/g) when compared with the aqueous leaves extract (30 mg gallic acid equivalents/g). The ethanol leaves extract was also found to have higher TFC (101 mg Catechin equivalents/g) than the aqueous leaves extract (76 mg Catechin equivalents/g). The ethanol leaves extract was then used for further chemical analysis. The LC–TOF-MS/MS analysis showed that the leaves extracts of O. indicum contains many important compounds such as Orientin, Chrysin, Pinoquercetin, Cupressuflavone, Puerarin xyloside, Forsythiaside and Paederoside. In GC-MS analysis, 19 compounds were identified in ethanolic leaves extract. The wound healing studies shows that O. indicum has promising wound healing activity by increasing the rate of wound contraction significantly (p<0.05). Conclusion: In conclusion, the present study showed that O. indicum leaf contains important phytochemicals and and the wound healing potential of the O. indicum extract may probably be as a result of the presence of various phytoconstituents.